Accurate qPCR quantification in polymicrobial communities requires assessment of gDNA extraction efficiency - Cerca, Nuno (2022)
qPCR absolute quantification requires the assessment of PCR reaction efficiency. This is achieved by performing serial dilutions of gDNA. Herein, we demonstrate that when quantifying bacterial load in mixed samples, reaction efficiency should not be used as a calibration curve since gDNA isolation efficiency is neglected, significantly impacting quantification.